Pemanfaatan sumber daya lokal biji karet sebagai amplifikasi protein es krim mellorine dengan pengemulsi CMC - Hidayat, Jefri Pandu; Pusfitasari, Memik Dian; Gunawan, Ryan Ananda Dwi; Fahlevi, Riza (AGROINTEK, 2025)
Rubber plants in East Kalimantan have a great plantation area 123,460 ha consisting of smallholder 95,240 ha, large state 3,630, and large private 25,638 hectares, with a total production of 55,690 tons. The abundant production of rubber plants in East Kalimantan is still utilized in the tree trunk part as raw material for making latex. The rubber seeds as dregs have not been optimally utilized. Rubber seeds are relatively high in nutrition, especially protein content 16.33%, 21.6% fat, and 30.9% carbohydrates. The rubber seeds are less optimally used due to high HCN levels. The possibility diversification of rubber seed is employing the mellorine ice cream. This study aims to analyze the decreasing HCN levels in the boiling time of rubber seeds at (0, 30, 60, 90, and 100 minute) and formulation of rubber seed and water ratio (A1-3:1); (A2-1,5:1); (A3-1:1) by complete randomized design (CRD) on proximate and organoleptic properties. It was found by ANOVA that the proportion of ingredients did not affect the organoleptic color and aroma but significantly swayed the texture and taste. The organoleptic scale is (0-5) and is not within the very likely criteria. The ratio prescription influences mellorine ice cream's physicochemical, where the more rubber seeds used, the higher proximate levels. The best formulation is A1 (3:1), where it gets an organoleptic value of color (4.25), aroma (3.5), texture (4.00), taste (4.40), 0.127% ash content, fat 8.36%, protein 1.57%, carbohydrate 9.08 %, and crude fibre 0.50%. Ultimately, the rubber seeds can be processed into protein source materials for mellorine ice cream, but the protein is still below SNI standards. A modification method is needed to release HCN but does not cause excessive protein denaturation.